Methods of test for sodium tripolyphosphate (pentasodium triphosphate) and sodium pyrophosphate (tetrasodium pyrophosphate) for industrial use. Determination of total phosphorus (V) oxide content: quinoline phosphomolybdate gravimetric method Part 10, (30th June 1976) - British Standards Institution,
No abstract available